Characterization of chemical composition and bacterial community of corrosion scales in different drinking water distribution systems. Issue 1 (6th December 2016) - Wang, Haibo; Hu, Chun; Yin, Lang; Zhang, Sujia; Liu, Lizhong
Abstract : There is a relationship between biochemical function and chemical composition of corrosion scales, and Fe3 O4 formation reduced iron release. Abstract : Characterization of the chemical composition and bacterial community of corrosion scales was studied in real drinking water distribution systems from eight cities. The results of X-ray powder diffraction (XRD) indicated that α-FeOOH and Fe3 O4 were present in all corrosion scales, and green rust was only found in corrosion scales of pipes transporting surface water. The corrosion scales with a higher Fe3 O4 /α-FeOOH ratio showed less iron release than those with a lower ratio. Moreover, the results of 454 pyrosequencing revealed that Proteobacteria (46.5–84.3%) was the main bacterial phylum in all corrosion scales; however, the bacterial genera were very different in the pipes from eight cities. Nitrate-reducing bacteria (10.9–36.0%) were the main potential corrosive bacteria, and denitrifying genes including nirS, nirK and nosZ were all found in the corrosion scales. The results of most probable number (MPN) tests indicated that nitrate-reducing bacteria, Fe(iii )-reducing bacteria and nitrate-dependent Fe(ii )-oxidizing bacteria in corrosion scales were indeed active and had the function of Fe(ii ) oxidation and Fe(iii ) reduction. All the results suggested that there was an apparent relationship between the relevant biochemical functions ( e.g., iron redox cycling) of the bacterial community and the formation of α-FeOOH and Fe3 O4 in corrosion scales. Furthermore, the relative abundance of Desulfovibrio also correlated very well with the content of green rust in corrosion scales. These results will be very helpful for future control of iron release in water distribution systems.